Analysis of 'Amil Nashab in Al-Qur'an Juz 1 and Its Implementation in Qawa'id Learning: Analisis ‘Amil Nashab dalam Al-Qur’an Juz 1 dan Implementasinya pada Pembelajaran Qawa’id - Muhammad Afif Hidayat; Imam Fauji (Universitas Muhammadiyah Sidoarjo, 2021)
This study aims to analyze the 'amil nashab contained in the Qur'an juz 1 and its implementation in qawa'id learning in class 8D SMP Muhammadiyah 3 Waru. This research uses descriptive qualitative research. And data collection techniques were carried out through observation, interviews and documentation.The results of this study are: in the science of qawa'id there are 8 kinds of amil nashab, namely: أن، لن، إذن، كى، لام التعليل، لام الجحود، حتى، الجواب بالفاء والواو. As for what is contained in the Qur'an juz 1 is as much as 4 kinds, namely: أن، لن، لام التعليل، حتى. The method used in learning qawa'id in Arabic subjects at SMP Muhammadiyah 3 Waru is deductive in nature (qiyasi), which is a method that begins with the presentation of the rules and then examples. In the learning process the teacher explains about 'Amil Nashab to students using power point learning media and in addition to providing examples from books the teacher also looks for examples from the verses of the Qur'an.